Kebijakan Pemerintah Dalam Perlindungan Hak Kekayaan Intelektual (HAKI) Di Indonesia - Laksminarti Laksminarti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This research aims to obtain a picture of the policy in the field of intellectual property rights as well as legislation and law enforcement of intellectual Property Rights (HAKI). The increasingly high-flow of free trades that demand the higher creativity of the resulting products proved increasingly spur on the technological developments that support these needs. Along with this, it began to realize the importance of the role of intellectual Property Rights (HAKI) in supporting technological developments. This is seen from the increasingly high number of copyright, patent and trademark applications and the sufficient number of industrial design applications addressed to the Directorate General of Intellectual Property Rights, the Office of the jurisdiction and human rights. By using a descriptive analysis obtained the idea that the implementation of good intellectual property rights system not only requires the legislation in the field of intellectual property right but should be supported also by Administration, law enforcement and an optimal socialization program on intellectual property Rights (HAKI). The results of the research show that at this time, Indonesia has had a legal device in the field of intellectual property rights which is adequate and does not contradict the provisions as required in Agreement on Trade-Related Aspect Of Intelectual Property Rights. In principle, all rules of intellectual property rights have been prepared about the interests of the Community and by the minimum provisions as required by TRIPS approval (Agreement on Trade-Related) Aspect Of Intelectual Property Rights).